2008
DOI: 10.1291/hypres.31.7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Effects of Olmesartan and Telmisartan on Blood Pressure and Metabolic Parameters in Japanese Early-Stage Type-2 Diabetics with Hypertension

Abstract: Olmesartan lowered mean systolic and diastolic blood pressure more significantly than did telmisartan.While there were no differences between the groups in metabolic parameters, including HbA1c and adiponectin, the decreases in serum interleukin-6 and highly sensitive C-reactive protein were more significant by olmesartan treatment. Our results indicate that olmesartan has more potent arterial blood pressure lowering and anti-inflammatory effects than telmisartan. (Hypertens Res 2008; 31: 7-13)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
71
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(77 citation statements)
references
References 38 publications
4
71
1
1
Order By: Relevance
“…The present study demonstrated that olmesartan significantly reduced serum hsCRP levels as previously reported. 25,[45][46][47] However, the changes in hsCRP levels were not associated with those in FMD. As in the case of microalbuminuria, as RAS inhibition produces pleiotropic effects, there may not be a simple one-to-one correlation between serum hsCRP levels and endothelial function either.…”
Section: Discussionmentioning
confidence: 90%
“…The present study demonstrated that olmesartan significantly reduced serum hsCRP levels as previously reported. 25,[45][46][47] However, the changes in hsCRP levels were not associated with those in FMD. As in the case of microalbuminuria, as RAS inhibition produces pleiotropic effects, there may not be a simple one-to-one correlation between serum hsCRP levels and endothelial function either.…”
Section: Discussionmentioning
confidence: 90%
“…[37][38][39] ARBs, particularly telmisartan and olmesartan, also exert antidiabetic effects through their regulation of insulin sensitivity and reduce not only urinary albumin excretion but also urinary 8-OHdG and L-FABP excretion. 40 Statins have been shown to ameliorate tubular and podocyte injury, preserve GFR and reduce proteinuria in renal disease. 41,42 In the present study, although all subjects were already treated with the maximal recommended dose of the ARB olmesartan, and there was no significant difference in the number of patients treated by statins at baseline between the two groups, further reduction in high-sensitivity CRP, urinary 8-OHdG and L-FABP levels was obtained.…”
Section: Discussionmentioning
confidence: 99%
“…13 Such findings are inline with in vitro studies, which show that OM produces a strong blockade of the AT 1 receptor, with a high degree of insurmountable binding, slow dissociation and high affinity for the AT 1 receptor. 14 The clinical consequences of this robust inhibition of the AT 1 receptor appear as the sustained reductions in SBP and DBP over 24 h seen in the metaanalysis of Fabia et al 7 Direct clinical comparisons in which OM produced larger reductions in BP measured by ABPM than several other ARBs may also reflect stronger AT 1 receptor blockade [15][16][17] The 2009 re-appraisal of the ESH-ESC guidelines on hypertension management acknowledge that, in general, in up to 20% of patients with hypertension BP control cannot be achieved by a two-drug combination. 4 However, even treatment with an ARB with superior AT 1 receptor binding characteristics may not lead to high rates of BP goal achievement in a population that includes a high proportion of patients with severe hypertension.…”
Section: Discussionmentioning
confidence: 99%